Взаимоотношение человека и природы на территории Пермского края в позднем плейстоцене и первой половине голоцена (100000-5300 лет назад) - Стенно (Stenno Sergey), Cергей Петрович; Циберкин (Tsiberkin Nicholas), Николай Григорьевич; Садовникова (Sadovnikova Elena), Елена Николаевна (Географический вестник=Geographical bulletin, 2017)
Рассматривается история взаимоотношений человека и природы на территории Пермского края в позднем плейстоцене и первой половине голоцена. Прослеживаются пути заселения территории Прикамья древним человеком. Описывается влияние первых поселений людей на природу в период палеолита, мезолита, неолита. THE INTERRELATIONS OF MAN AND NATURE ON THE TERRITORY OF PERM REGION IN LAST PLEISTOCENE AND IN THE FIRST HALF OF HOLOCENIC SYSTEM (100 000 – 5300 YEARS AGO) The whole history of nature in theKamaarea can be divided into two periods. In the first period (100000-5300 years ago) among the peoples of theKamaarea dominated by assigning the type of nature: hunting, gathering and fishing. The impact of man on nature manifested itself at the local level, covering some of the natural complexes of low taxonomic rank or its individual components. Depth of impact on natural systems as a whole was negligible. But for the individual components of the landscape and, especially for certain species of flora and fauna, it had eliminates the value. Sometimes the change of natural environments enhanced the human impact, but the results of nature that period as a whole did not have significant consequences for the nature of Perm Kama in theAtlanticafter time.